Fluorescence to measure light intensity - Lahlou, Aliénor; Tehrani, Hessam Sepasi; Coghill, Ian; Shpinov, Yuriy; Mandal, Mrinal; Plamont, Marie-Aude; Aujard, Isabelle; Niu, Yuxi; Nedbal, Ladislav; Lazár, Dusan; Mahou, Pierre; Supatto, Willy; et al. (Nature methods, 2023)
Despite the need for quantitative measurements of light intensity across many scientific disciplines, existing technologies for measuring light dose at the sample of a fluorescence microscope cannot simultaneously retrieve light intensity along with spatial distribution over a wide range of wavelengths and intensities. To address this limitation, we developed two rapid and straightforward protocols that use organic dyes and fluorescent proteins as actinometers. The first protocol relies on molecular systems whose fluorescence intensity decays and/or rises in a monoexponential fashion when constant light is applied. The second protocol relies on a broad-absorbing photochemically inert fluorophore to back-calculate the light intensity from one wavelength to another. As a demonstration of their use, the protocols are applied to quantitatively characterize the spatial distribution of light of various fluorescence imaging systems, and to calibrate illumination of commercially available instruments and light sources. Two methods for fluorescence-based actinometry using organic dyes and photoconvertible fluorescent proteins enable rapid and precise measurement of light intensity at the sample in fluorescence microscopes.